Synthesis and analysis of the all-(S) side chain of phosphomycoketides: a test of NMR predictions for saturated oligoisoprenoid stereoisomers - Buter, Jeffrey (2013)
(4S,8S,12S,16S,20S)-Pentamethylheptacosan-1-ol has been synthesized and analyzed by resolution-enhanced NMR spectroscopy with the aid of a recent set predicted spectra of all its stereoisomers. The configuration was confirmed but isomer purity of the sample (~70%) was lower than expected. A truncated analog, (2S,6S,10S,14S)-2,6,10,14-tetramethylhenicosan-1-ol TBDPS ether, was prepared from a late stage synthetic intermediate. Analysis of its spectra confirmed the configuration and showed that the sample was isomerically pure. The results suggest that a late-stage epimerization, not a failure of an asymmetric synthesis step, caused the formation of minor stereoisomers in the sample of pentamethylheptacosan-1-ol. The study shows the value of the predicted set of oligoisoprenoid spectra and further extends the predictive model to a new subclass of compounds.